solve the system using any algebraic method
asked Nov 17, 2011 in Algebra 2 Answers by anonymous

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

1) 2x - 5y = 4

2) 3x + 4y = 9

multiply eq(1) by 3 and eq(2) by -2, add:

 6x  -  15y  =  12

-6x  -   8y   = -18

_____________

         - 23y  =  -6

y = 6/23

using eq(1):

2x - 5(6/23) = 4

2x - 30/23 = 4

2x = 4 + 30/23 = 92/23 + 30/23 = 122/23

x = 61/23

check using eq(2):

3(61/23) + 4(6/23) = 9

183/23 + 24/23 = 9

9 = 9

x = 61/23, y = 6/23
answered Nov 17, 2011 by Battleaxe Level 6 User (23,120 points)
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
76,953 questions
80,417 answers
1,582 comments
58,205 users